2013
DOI: 10.1021/ef400965m
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Saturates, Aromatics, Resins, and Asphaltenes Fractions in the Bituminous Layer of Athabasca Oil Sands

Abstract: The composition and distribution of saturates, aromatics, resins, and asphaltenes (SARA) fractions in the bituminous layer on the surface of Athabasca oil sands were identified using elemental analysis (EA), X-ray photoelectron spectroscopy (XPS), field emission scanning electron microscopy (SEM) with an energy-dispersive spectrometer (EDS), and Fourier transform infrared spectrometry (FTIR). The contents of elements sulfur (S) and nitrogen (N) and the ratios of carbon/ sulfur (C/S) and carbon/nitrogen (C/N) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 52 publications
1
32
1
1
Order By: Relevance
“…In this study, two representative asphaltene models were selected including the continental asphaltene (ASP1, C 54 H 65 NO 2 S) and the Violanthrone-79 asphaltene (ASP2, C 50 H 48 O 4 ). The selection of these two models was inspired by the facts that (i) the asphaltene samples in our laboratory experiments originated from heavy crude oil and Athabasca oil sands bitumen (Li et al, 2012a;He et al, 2013), (ii) the asphaltenes extracted from crude oil were proved to be consistent with the continental asphaltene model (Durand et al, 2008), (iii) the properties of Violanthrone-79 model were demonstrated consistent with the Athabasca bitumen asphaltene (López-Linares et al, 2006), and (iv) both models have been successfully used to simulate the asphaltene aggregation process (Ruiz-Morales and Schneider et al, 2007;Kuznicki et al, 2009). The Leonardite humic acid model (LHA, C 31 H 26 O 12 ) was used in this study (Fig.…”
Section: Molecular Modelsmentioning
confidence: 99%
“…In this study, two representative asphaltene models were selected including the continental asphaltene (ASP1, C 54 H 65 NO 2 S) and the Violanthrone-79 asphaltene (ASP2, C 50 H 48 O 4 ). The selection of these two models was inspired by the facts that (i) the asphaltene samples in our laboratory experiments originated from heavy crude oil and Athabasca oil sands bitumen (Li et al, 2012a;He et al, 2013), (ii) the asphaltenes extracted from crude oil were proved to be consistent with the continental asphaltene model (Durand et al, 2008), (iii) the properties of Violanthrone-79 model were demonstrated consistent with the Athabasca bitumen asphaltene (López-Linares et al, 2006), and (iv) both models have been successfully used to simulate the asphaltene aggregation process (Ruiz-Morales and Schneider et al, 2007;Kuznicki et al, 2009). The Leonardite humic acid model (LHA, C 31 H 26 O 12 ) was used in this study (Fig.…”
Section: Molecular Modelsmentioning
confidence: 99%
“…Bitumen is known to be a complex mixture of natural organic molecules, containing different aliphatic, cyclic and aromatic building blocks with a number of heteroatoms (such as oxygen, sulfur and nitrogen) and heavy metals (e.g., V, Ni) (He et al, 2013;Yoon et al, 2009a;Yoon et al, 2009b). Based on the results and discussions above, the interactions between solvent-diluted bitumen and air bubbles in the process water could be described as follows.…”
Section: Adsorption Mechanismmentioning
confidence: 99%
“…As far as bitumen composition is concerned, analyses based on infrared spectroscopy and elemental analysis of saturates, aromatics, resins, and asphaltenes (SARA) fractions, extracted sequentially from oil sands, suggested that these are not evenly distributed throughout the bitumen layers, with the most polar asphaltene and resin species being concentrated at the sand surfaces [11].…”
Section: Oil Sands Structure and Compositionmentioning
confidence: 99%